A point mutation in the extracellular domain of CD4 completely abolishes CD4 T cell development in C57BL/6 mouse. (December 2017) - Wang, Huijie; Li, Saichao; Chao, Tianzhu; Wang, Xugang; Shi, Lijin; Zhang, Lichen; Liang, Yinming; Zheng, Qianqian; Lu, Liaoxun
Highlights: An ENU induced mutant mouse with CD4 T lymphocyte deficiency. Identification of the causative mutation in the T cell deficient mice. The isoleucine to asparagine mutation at the position of 99 of CD4 does not affect its surface expression. The ENU induced CD4 deficient mouse is a desirable model for studies involving CD4 T cell transfer. Abstract: In this study, we performed ENU mutagenesis and multi-parameter flow cytometric analysis in C57BL/6 mice to uncover novel genes or alleles regulating immune cell development. We identified a novel mutant allele of Cd4 gene which completely blocked development of a major subset of T cells named CD4 T cell. Our data for the first time showed experimentally in mice the critical role of the first extracellular domain, by obtaining mice with a loss of function mutation from Ile to Asn at the position 99 of CD4 (I99N). Interestingly, such CD4 I99N mutant protein can be expressed on the surface of human cells, and the mRNA stability could be also affected by this point mutation, suggesting that absence of CD4 T cells in mice rooted in the deficiency in function and expression of CD4. In addition, we used this novel CD4 T cell deficient model as recipient mice for adoptive transfer experiment, and showed that it could be an optimal model for study of CD4 T cells.